Le mystère de Crawford Park-(Partie 3) - Voisine, John (Les Argoulets, 2024)
Keywords: Logement; Quartiers; Verdun

Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

La Belle Centenaire - Bolduc, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Logement; Patrimoine; Sault-au-Récollet

Le parc Molson et ses abords - Bouchard-Dupont, Maude (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Parcs; Rosemont

L'église Saint-Arsène il était une foi... - Desautels, Stéphanie (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Rosemont; Églises

Un aperçu des résidents du Parc Amherst 1892-1921 - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Locataires; Logement; Rosemont

Le 1035 rue de Bellechasse: une coopérative trentenaire dans un bâtiment centenaire - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Coopérative d'habitation de Montréal; Rosemont

La Halte de La Visitation - Goulet, Patrick (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: La Visitation (église); Patrimoine; Sault-au-Récollet

Une victorienne bien cachée! - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Famille; Logement; Sault-au-Récollet

Proprety and Power: Connecting the Dots - Olson, Sherry (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Dans la rue. Une histoire du FRAPRU et des luttes pour le logement au Québec - Saillant, François (Écosociété, 2024)
Keywords: Groupes populaires; Logement

Gender and Social Relations in the City above the Hill - Sweeny, Robert C.H. (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Femmes; Golden Square Mile; Quartiers

Le bungalow, un témoin de l'histoire d'Anjou - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
Keywords: Anjou; Banlieue

Westmount Station: Canadian Pacific history and future visioning - Hanna, David B. (The Westmount Historian, 2023)
Keywords: Canadien Pacifique; Commémoration; Gares

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

Ucal-Henri Dandurand et la pratique des ventes de sociétés immobilières à Montréal, au tournant du XXe siècle - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2023)
Keywords: Publicité

La British and Canadian School de Montréal - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)

La propriété en conflit: Justice et droit du logement à Montréal (1941-1980) - Mercier, Ian (Université du Québec à Trois-Rivières, 2023)
Keywords: Droit; Logement; Tribunaux

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

Des origines à la Dépression. Quartier Crawford Park- (Partie 2) - Voisine, John (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Quartiers; Verdun

La carrière Rhéaume 1909-1937 - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Carrière; Rosemont

Marion Nelson Crawford, la partenaire du notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Crawford, Alexander

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

TRUDEAU, JOSEPH-CHARLES-ÉMILE - English, John (Dictionnaire biographique du Canada, 2022)

La Ligue ouvrière catholique et la naissance de la paroisse Saint-André-Apôtre (première partie) - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Famille; Jeunesse ouvrière catholique (JOC); Ligue ouvrière catholique; Logement; Quartiers

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Logement

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Montréal, Hospitable Capital City - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Hôtellerie; Marchés

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

Vivre dans une boîte à chaussure - Poitras, Jean (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Logement

Going Together Like a Horse and Carriage: Rentier Marriages and Property Accumulation in Montréal, 1825-1903 - Sweeney, Robert C. H. (Histoire sociale / Social History, 2021)
Keywords: Famille; Logement; Mariage

L'énigmatique maison de ferme de la 23e avenue - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Logement

Le docteur Ananie-Joseph Millier, un notable rosemontois méconnu - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Logement; Médecine; Quartiers; Rosemont

Alexander Crawford, le notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Crawford, Alexander

L’action des promoteurs immobiliers dans le processus de gentrification du Sud-Ouest de Montréal - Gaudreau, Louis; Houle, Marc-André; Fauveaud, Gabriel (Recherches sociographiques, 2021)
Keywords: Arrondissements; Gentrification; Le Sud-Ouest; Logement

Soutien et entraide. Les mouvements coopératifs et communautaires du Plateau de 1970 à 2000 (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
Keywords: Clinique des citoyens de Saint-Jacques; Cyclisme; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Le marché Sainte-Anne et ses eaux souterraines. Imaginer et construire de façon innovatrice - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Sainte-Anne (marché)

Les premières maisons shoebox montréalaises de Rosemont et de Villeray - Gaudreau, Guy (Urban History Review / Revue d'histoire urbaine, 2021)
Keywords: Quartiers; Rosemont; Villages; Villeray

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Famille; Logement; Quartiers; Rosemont

Louis-Joseph Papineau’s Seigneurialism, Republicanism, and Jeffersonian Inclinations - Guimond, Olivier (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
Keywords: Idéologies; Papineau, Louis-Joseph; Rébellions; Seigneurie

Ateliers à louer, le " phalanstère " d'Alfred Laliberté - Lacroix, Laurier (Les Cahiers des Dix, 2021)
Keywords: Laliberté, Alfred; Locataires; Logement; Peinture; Sculpture

COHEN, LYON - Lapidus, Steven (Dictionnaire biographique du Canada, 2021)

The Making of Habitat 67. A Tense Pas de Deux between Moshe Safdie and August Komendant - Legault, Réjean (Journal of the Society for the Study of Architecture in Canada / Le journal de la Société d'étude pour l'architecture au Canada, 2021)
Keywords: Béton; Expositions; Logement

Enjeux politiques de la frontière entre salubrité et insalubrité dans l'habitation montréalaise des années 1930 - Racette, Jean-Christophe (Revue d'histoire de l'Amérique française, 2021)
Keywords: Crise; Logement; Pauvreté

1844-1849. Montréal, nouveau siège du gouvernement - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Montréal, capitale accueillante - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Hôtellerie; Marchés

Luttes pour le droit au logement sur le Plateau - Vallée, Bernard (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
Keywords: Crise; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Le rôle méconnu des promesses de vente dans le processus d'urbanisation à Montréal: le cas du village de Villeray au tournant du XXe siècle - Gaudreau, Guy (Urban History Review / Revue d'histoire urbaine, 2020)
Keywords: Villages; Villeray

Divvying up Space: Housing Segregation and National Identity in Early Twentieth-Century Montréal - Sweeny, Robert C. H. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Locataires; Logement; Quartiers

1840-1912: De la montée du Sault à la rue Lajeunesse: sept décennies de chemins de barrières... et quelques incendies - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Keywords: Incendies; Routes; Rues

La première couronne montréalaise est sertie de maisons shoebox (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2019)
Keywords: Conservation; Logement; Patrimoine; Quartiers; Rosemont

Carrières et pierre grise (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
Keywords: Carrière; De Lorimier (village); Géographie physique; Géologie; Histoire naturelle; Parcs; Plateau Mont-Royal; Quartiers; Travail; Villages; Églises

LAURIN, JAMES - Auger, Jean-François (Dictionnaire biographique du Canada, 2019)

"C'est providentiel!". Vendre le rêve suburbain à Montréal (1950-1970) - Bérubé, Harold (Cap-aux-Diamants, 2019)
Keywords: Banlieue; Publicité

" De la fiction à… la réalité – de la télévision à… Laval-des-Rapides ": Mise en récit et mise en marché du rêve suburbain à Montréal, 1950–1969 - Bérubé, Harold (Quebec Studies, 2019)
Keywords: Banlieue; Laval-des-Rapides; Publicité

La petite histoire, des origines jusqu'à 1925. Des carrières sous le parc Laurier - Côté, Julie; Cudia, Caroline (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
Keywords: Carrière; Parcs; Travail

FORTIN, SIFROY-JOSEPH - Fougères, Dany; Gagnon, Robert (Dictionnaire biographique du Canada, 2019)

Communauté Milton-Parc: How We Did It and How It Works Now - Kowaluk, Lucia; Piché-Burton, Carolle (Villages in cities: community land ownership, cooperative housing, and the Milton Parc story, 2019)
Keywords: Logement; Milton-Parc; Quartiers

MIGNAULT, ARTHUR - Litalien, Michel (Dictionnaire biographique du Canada, 2019)

Montreal Property-Owners of the 1850s: "Born or to Be Born" - Olson, Sherry (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Keywords: Droit; Enfants; Famille; Logement

The influence of urban design theories in the transformation of urban morphology: Montreal from 1956 to 2018 - Racine, François (Journal of Urban Design, 2019)
Keywords: Logement; Quartiers

CURRY, NATHANIEL - Sutherland, David A. (Dictionnaire biographique du Canada, 2019)

Introducing Canada to Urban Planning? Henry Vivian's Canadian Planning Tour, 1910 - Ulmer, Catherine Mary (Urban History Review / Revue d'histoire urbaine, 2019)
Keywords: Logement

" Je me souviens " d’un domaine seigneurial à Ahuntsic - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Keywords: Ahuntsic; Communautés religieuses; Domaine Saint-Sulpice; Logement; Seigneurie; Sulpiciens

L'école Sainte-Odile: au coeur du "nouveau Cartierville" - M. Sénécal, Geneviève (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Keywords: Cartierville; Logement; Parcs; Quartiers; Rues

The Second World War: Wartime Production and War Efforts - Fahrni, Magda (Montreal: The History of A North American City, 2018)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

The Modern City: 1840-1890 - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

The years of dispersion - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Permanence et renouvellement des familles ouvrières: le cas du Village-aux-Oies et de la rue Forfar, 1901-1921 - Giguère, Charles-Robert (Université du Québec à Montréal, 2018)
Keywords: Famille; Locataires; Logement; Mobilité résidentielle; Villages

Denis-Benjamin Viger (1774-1861). Patriote assagi par la richesse sans en être aveuglé - Lavallée, Martin (Montréal en tête, 2018)
Keywords: Foretier, Pierre; Seigneurie; Testaments; Viger, Denis-Benjamin

Mount Royal: The Top of the Island - MacLeod, Roderick (Montreal: The History of A North American City, 2018)
Keywords: Mont Royal; Mont-Royal (parc); Parcs

La grève générale des charpentiers-menuisiers de Montréal, 1833–1834 : réévaluation d’un acte fondateur autour du concept de légitimité - Tremblay, Robert (Labour / Le travail, 2018)
Keywords: Charpentiers; Grèves; Libéralisme; Maçons; Menuisiers

On the Ruins of Hochelaga: 1535-1650 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Autochtones; Cartier, Jacques; Chomedey de Maisonneuve, Paul (Maisonneuve, Paul de Chomedey de); Fourrure; Français; Hochelaga; Iroquoiens; Iroquois; Mance, Jeanne; Société de Notre-Dame de Montréal

La Montreal Investment Association, le Montreal Investment Trust et la seigneurie de Beauharnois (1866–1941) - LaRose, André (Canadian Historical Review, 2017)
Keywords: Fiducie

L'architecture du Plateau Mont-Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2017)
Keywords: Carmélites; Communautés religieuses; Logement; Plateau Mont-Royal; Quartiers; Églises

Cinquante ans de développement de la fonction résidentielle dans le Vieux-Montréal et les anciens faubourgs: quelles leçons en tirer ? - Ananian, Priscilla (Environnement Urbain / Urban Environment, 2017)
Keywords: Faubourgs; Logement; Quartiers; Vieux-Montréal

Vendre la banlieue aux Montréalais: discours et stratégies publicitaires, 1950-1970 - Bérubé, Harold (Revue d'histoire de l'Amérique française, 2017)
Keywords: Anglophones; Banlieue; Francophones; Publicité

Corruption politique et clientélisme à Montréal de 1996 à 2011 : forces et dynamiques des institutions formelles et informelles à la lumière des travaux de la Commission Charbonneau - Gagné, Benoit (Université du Québec à Montréal, 2017)
Keywords: Maires

Contrôler le logement, contrôler la Ville: l’intervention en matière de salubrité des logements à Montréal, 1930-1939 - Racette, Jean-Christophe (Université de Montréal, 2017)
Keywords: Crise; Logement; Pauvreté

Les syndicats internationaux dans l’industrie de la construction au Québec (1887–1930) - Rouillard, Jacques (Labour / Le travail, 2017)
Keywords: Charpentiers; Confédération des syndicats nationaux; Conseil des métiers et du travail de Montréal; Fédération des travailleurs et travailleuses du Québec (FTQ); Menuisiers

Expo 67: le choix du site et la forme des îles - Legault, Réjean (ARQ - Architecture Québec, 2016)
Keywords: Expositions

Repurposing buildings (The Westmount Historian, 2016)
Keywords: Conservation; Gares; Logement; Patrimoine

Apartment housing then and now: vignettes from Toronto and Montreal - Dennis, Richard (British Journal of Canadian Studies, 2016)
Keywords: Conservation; Logement

Tragédie à LaSalle: l'explosion du 1er mars 1965 - Gravel, Denis; Boucher, Isabelle (Société historique Cavelier-de-LaSalle, 2016)
Keywords: Arrondissements; Incendies; LaSalle; Logement

Seigneur absent, seigneur effacé? Louis-Joseph Papineau et la gestion de la Petite-Nation par l’entremise de Denis-Benjamin, son frère et agent seigneurial (1817-1854) - Guimond, Olivier (Histoire Québec, 2016)
Keywords: Papineau, Louis-Joseph; Seigneurie

Le père du célèbre Louis-Joseph Papineau: Joseph Papineau, premier en tout - Aubin, Georges (Montréal en tête, 2015)
Keywords: Arpenteurs; Notaires

Shaping Time in the City: A Cultural History of Concrete Modernity in Montreal, 1903-2015 - Charles, Julia Morgan (Université McGill, 2015)
Keywords: Autoroutes; Béton; Port; Stade olympique

William Zeckendorf, Place Ville-Marie, and the Making of Modern Montreal - Nerbas, Don (Urban History Review / Revue d'histoire urbaine, 2015)
Keywords: Gratte-ciel; Place Ville-Marie

La gestion seigneuriale de l'île de Montréal par les Sulpiciens au XVIIe siècle - Martel, Stéphan (Montréal en tête, 2014)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

CURRIE, sir ARTHUR WILLIAM - Cook, Tim (Dictionnaire biographique du Canada, 2013)

Seigneurs and Landowners: An Ecclesiastical Economic Vision - Dickinson, John A. (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Une plongée vertigineuse dans l'histoire sociale de l'île de Montréal. Autour de la maison Brignon-Lapierre - Lapierre, Michel (Montréal en tête, 2013)
Keywords: Brignon-Lapierre (famille); Rébellions

Making Co-opville: Layers of Activism in Point St-Charles (1983-1992) - Vickers, Simon (Université Concordia, 2013)
Keywords: Groupes populaires; Pointe-Saint-Charles; Quartiers

La Deuxième Guerre mondiale: territoires d'armement et de l'effort de guerre - Fahrni, Magda (Histoire de Montréal et de sa région, 2012)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

La ville moderne, 1840-1890 - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

Les années de dispersion - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Implantation d'un prototype de tableau de bord de gestion à la direction de soutien à la gestion de la Fédération des coopératives d'habitation intermunicipale du Montréal Métropolitain (FECHIMM) - Koffi, Yao Kouma (École nationale d'administration publique, 2012)

Sur les décombres d'Hochelaga, 1535-1650 - Viau, Roland (Histoire de Montréal et de sa région, 2012)
Keywords: Autochtones; Cartier, Jacques; Chomedey de Maisonneuve, Paul de (Maisonneuve, Paul de Chomedey de); Fourrure; Français; Hochelaga; Iroquoiens; Iroquois; Mance, Jeanne; Société de Notre-Dame de Montréal

Corner of Victoria Avenue & Sherbrooke (The Westmount Historian, 2011)
Keywords: Banque Royale; Banques; Magasins; Rues; Sherbrooke (rue)

La maison et ses dépendances (Les Argoulets, 2011)
Keywords: Nivard-De-Saint-Dizier (maison); Seigneurie; Verdun

Les différents propriétaires et leur histoire (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Keywords: Chapman, Joseph; Congrégation de Notre-Dame; Crawford, John; Dupuy, Zacharie; Greater Montreal Land Company; Logement; Nivard de Saint-Dizier, Marie-Anne; Nivard de Saint-Dizier, Étienne; Nivard-De-Saint-Dizier (maison); Steward Hunter, William; Verdun

Enforcing the Right to Healthy Housing: Recourse for Montreal Tenants Facing Health and Safety Problems at Home - Auchinleck, Jennifer (Université McGill, 2011)
Keywords: Locataires; Logement

L’opération 5000/15000 logements sociaux et communautaires: Une réponse au besoin en logements des ménages immigrants récents à Montréal, le cas de Côte-des-Neiges - Bahlouli, Abdelaziz (Université de Montréal, 2011)
Keywords: Côte-des-Neiges; Logement; Quartiers

L'évolution du capital immobilier au centre-ville de Montréal - Bernier, Lyne (Université du Québec à Montréal, 2011)
Keywords: Centre-ville; Quartiers

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

Les premiers immeubles d’appartements de Montréal, 1880–1914. Un nouveau type d’habitation - Huppé, Isabelle (Urban History Review / Revue d'histoire urbaine, 2011)
Keywords: Logement

La naissance d'un fief: Verdun - Loiselle, François (Les Argoulets, 2011)
Keywords: Seigneurie; Verdun

City Streets as Environmental Grid: The Challenge of Private Uses and Municipal Stewardship - Olson, Sherry (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Rues

Cinémas d’après-guerre - Pageau, Pierre (Continuité, 2011)
Keywords: Cinéma

L'attrait pour le modèle de l'enclave résidentielle sécurisée dans la région montréalaise. que nous révèle le discours publicitaire sur le logement neuf? - Séguin, Anne-Marie (Cahiers de géographie du Québec, 2011)
Keywords: Logement

La maison et ses dépendances - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Keywords: Conservation; Patrimoine

Victoria Avenue in Westmount (The Westmount Historian, 2010)
Keywords: Casernes; Gares; Logement; Magasins; Rues; Westmount; Épicerie

Joseph Rielle (Riel). Maire de Verdun 1904-1905 - Billard, Guy (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2010)
Keywords: Arpenteurs; Maires; Quartiers; Verdun

Propriétaires et promoteurs à LaSalle: plus d'un siècle d'évolution économique - Boucher, Bruno; Gravel, Denis (Société historique Cavelier-de-LaSalle, 2010)
Keywords: LaSalle; Logement

La concertation autour du projet immobilier Porte Sainte-Marie à Montréal: le pari de la collaboration en marge du processus habituel - Cloutier, Geneviève; Sénécal, Gilles (Lien social et Politiques, 2010)
Keywords: Centre-sud (quartier); Logement; Quartiers

A Comparison of Workforce Housing Practices in Three Cities and their Applicability to Montreal - Lazarovic, Rebecca (Université McGill, 2010)
Keywords: Logement; Travail

Les déterminants de la valeur dans le marché immobilier montréalais: étude appliquée aux lignes de distribution câblées, à la végétation et aux types de rue - Montpetit, Guillaume (Université du Québec à Montréal, 2010)
Keywords: Logement; Quartiers; Île-des-Soeurs

Providing a Home and then Some: A study of Montreal's Homeownership Programme - Pinches, Brendan James (Université McGill, 2010)
Keywords: Logement

Réinvestir dans l'histoire. Trente ans de promotion immobilière dans l'arrondissement historique de Montréal - Poitras, Claire (Le Vieux-Montréal, un "quartier de l'histoire"?, 2010)
Keywords: Patrimoine; Quartiers; Vieux-Montréal

Louise Paradis: une femme à la tête du domaine Saint-Gabriel des Sulpiciens - Blondin, Yves (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Baux à ferme; Communautés religieuses; Famille; Femmes; Saint-Gabriel (ferme); Sulpiciens

La petite histoire du moulin à eau de la rivière Saint-Pierre et de ses meuniers - Charlebois, Paul-Yvon (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Côtes; Meunerie; Sulpiciens

Château Ramezay: le passé continue - Delisle, André (Continuité, 2009)
Keywords: Cartes et plans; Ramezay (château de)

La ferme Saint-Gabriel des sulpiciens à la Pointe Saint-Charles. Partie I: le Régime français - Douaire, Gilles (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Pointe-Saint-Charles; Saint-Gabriel (ferme); Seigneurie; Sulpiciens

Reconstruire Montréal, rebâtir sa fortune - Dufaux, François; Olson, Sherry (Revue de Bibliothèque et Archives nationale du Québec, 2009)
Keywords: Faubourgs; Logement

L'accession à la propriété des jeunes familles à Montréal - Geoffroy, Caroline (École nationale d'administration publique, 2009)
Keywords: Logement

Investir, construire et habiter le monde. Les 25 ans de SITQ, histoire et perspectives - Marchand, Sarah; Linteau, Paul-André (Boréal, 2009)

Designing Sustainability for Whom? Recent Housing Development in Southwest Montreal - Poitras, Claire (Local Environment. The International Journal of Justice and Sustainability, 2009)
Keywords: Logement

Le légalisme à la sulpicienne - Savard, Rémi (Recherches amérindiennes au Québec, 2009)
Keywords: Autochtones; Communautés religieuses; Sulpiciens

Disputed Post-Industrial Landscapes: An Enquiry into the "Loft-Living" Cultural Model in Montréal's Saint-Henri - Tam, Edith (Université Concordia, 2009)
Keywords: Logement; Quartiers; Saint-Henri

Preservation of Westmount Homes built in the 1800s (The Westmount Historian, 2008)
Keywords: Conservation; Logement; Patrimoine; Quartiers; Westmount

WHA looks at some Prominent Westmounters (The Westmount Historian, 2008)
Keywords: Lait; Magasins; Port; Quartiers; Quincaillerie; Westmount

Les immeubles à appartements de l'île de Montréal, émergence et évolution d'une typologie, 1880-1914 - Huppé, Isabelle (Université du Québec à Montréal, 2008)
Keywords: Logement

Rapport sur la question du logement à Montréal; phase 2 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2008)
Keywords: Locataires; Logement; Pauvreté

L'héritage des soeurs des Saints-Nom de Jésus et de Marie à Outremont - Beauregard, Ludger (Histoire Québec, 2007)
Keywords: Communautés religieuses; Outremont; Quartiers; Soeurs des Saints Noms de Jésus et de Marie

Le Vieux-Montréal: une toute autre histoire - Chartrand, Roger (Septentrion, 2007)
Keywords: Quartiers; Vieux-Montréal

Seigneurs et propriétaires: une logique ecclésiastique de l'économie - Dickinson, John A. (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Conditions de logement des ménages immigrants et dynamiques métropolitaines à Montréal: une analyse multiniveau exploratoire - Leloup, Xavier (Cahiers québécois de démographie, 2007)
Keywords: Logement

Equality and Urbanism: An Inquiry on Egalitarian Ethics in Planning with a Particular Reference to the Public Consultation Policy and the Overdale Approach to Equal Land-Use Opportunities of the Montreal Citizen's Movement - Pyun, Jin-Bak (Université Concordia, 2007)
Keywords: Rassemblement des citoyens et citoyennes de Montréal

Rapport sur la question du logement à Montréal; phase 1 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2007)
Keywords: Locataires; Logement; Pauvreté

Benny Farm: une vocation renouvelée - Barberese, Dino (Continuité, 2006)
Keywords: Conservation; Logement; Patrimoine

Immeubles résidentiels à Montréal: l’art du compromis - Dufaux, François (Continuité, 2006)
Keywords: Logement

A Gentleman of Substance: The Life and Legacy of John Redpath (1796-1869) - Feltoe, Richard (Dundurn Press, 2006)
Keywords: Hommes d'affaires; Redpath Sugar; Redpath, John; Sucre

Valeur hédonique des terrains à usage résidentiel unifamilial sur l'île de Montréal - Özdilek, Unsal (Université de Montréal, 2006)

The Affordable Housing Market in Montréal: a Market Analysis and Applicability Study of Inclusionary Zoning - Wang, Yun (Université de Montréal, 2006)
Keywords: Logement

Property Developers and the Robust Downtown: the Case of Four Major Canadian Downtowns - Charney, Igal (The Canadian Geographer / Le Géographe canadien, 2005)

Le Domaine. Une belle histoire qui se poursuit... Les loisirs du Domaine - Archambault-Malouin, Diane (Les Services du Domaine Inc., 2005)
Keywords: Domaine Saint-Sulpice; La Familiale; Logement

Famille, affaires et succession, les enjeux de la gestion seigneuriale au Canada. Étude de la région montréalaise des 17e et 18e siècles - Couvrette, Sébastien (Histoire Québec, 2005)
Keywords: Famille; Seigneurie

Le logement traditionnel à Montréal et à Glasgow: partage et différence - Dufaux, François (Montreal-Glasgow, 2005)
Keywords: Logement

Une culture matérielle riche dans le « Red Light » de Montréal: Inventaire et fouille archéologiques au faubourg Saint-Laurent MTL03-25-3, MTL03-25-2 et BjFj-121, 2003: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2005)
Keywords: Faubourgs; Logement; Quartiers; Saint-Laurent (quartier)

Les marchés de construction notariés et les transformations de la sphère privée et de la sphère publique à Montréal entre 1700 et 1755 - Latouche, Pierre-Édouard (Université Laval, 2005)
Keywords: Notaires

On-Site Labor Productivity Estimation Using Neural Networks - Wang, Fang (Université Concordia, 2005)
Keywords: Travail

Le Domaine. Une belle histoire qui se poursuit... La Caisse du Domaine - Archambault-Malouin, Diane; Desbiens, Josée; Pronovost, Claude (Les Services du Domaine Inc., 2004)
Keywords: Banques; Caisses populaires; Desjardins, Alphonse; Domaine Saint-Sulpice; Logement

Le régime seigneurial à Montréal - Beaudoin, Léo (Montréal en tête, 2004)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

La dynamique spatiale du marché des bureaux dans la région métropolitaine de Montréal de 1987 à 2001 - Gignac, Yannick (Université de Montréal, 2004)

Architectes et ingénieurs actifs à Montréal dans les années 1960 - Lortie, André (Les années 60: Montréal voit grand, 2004)
Keywords: Ingénieurs

Architects and Engineers Active in Montreal in the 1960s - Lortie, André (The 60s: Montreal Thinks Big, 2004)
Keywords: Ingénieurs

Montréal 1960; les singularités d'un archétype métropolitain - Lortie, André (Les années 60: Montréal voit grand, 2004)
Keywords: Métropole

Montreal 1960: The Singularities of a Metropolitan Archetype - Lortie, André (The 60s: Montreal Thinks Big, 2004)
Keywords: Métropole

Risky Spaces : The Montreal Fire Insurance Company, 1817-20 - Sweeny, Robert C. H. (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Assurance; Incendies

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

La transmission du patrimoine seigneurial des familles du gouvernement de Montréal aux XVIIe et XVIIIe siècles - Couvrette, Sébastien (Université de Montréal, 2003)
Keywords: Famille; Notaires; Seigneurie

Le Domaine. Une belle histoire qui se poursuit... Trois coopératives... Tout un début! - Desbiens, Josée; Pronovost, Claude (Les Services du Domaine Inc, 2003)
Keywords: Chaurès-Louard, Berthe; Coopérative d'habitation de Montréal; La Familiale; Logement

La maison Bagg: inventaire archéologique au site BiFj-32, 1992: Vieux-Montréal et faubourgs - Ethnoscop (Patrimoine archéologique de Montréal, 2003)
Keywords: Logement; Marchands

L'habitation type. Évolution de l'immeuble locatif pour les quartiers ouvriers: le cas de Verdun - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
Keywords: Logement; Quartiers; Verdun

Patrimoine industriel: le souffle de l’art - Lord, Denis (Continuité, 2003)
Keywords: Patrimoine

The Road to Terrace Bank: Land Capitalization, Public Space, and the Redpath Family Home, 1837-1861 - Macleod, Roderick (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2003)
Keywords: Redpath (famille); Redpath, John

"Tuer le taudis qui nous tuera": crise du logement et discours sur la famille montréalaise d'après-guerre (1945-1960) - Bourbeau, Amélie (Université de Montréal, 2002)
Keywords: Logement; Pauvreté

Le déclin de la maison de fond de cour à Montréal, 1880–1920 - Carey, Luc (Urban History Review / Revue d'histoire urbaine, 2002)
Keywords: Logement

L'intervention municipale dans le développement résidentiel, l'opération Habiter Montréal 1990-2001 - Gomez, Élodie (Université de Montréal, 2002)
Keywords: Logement; Évaluation foncière

Battles on the Homes Front: Montreal's Response to Federal Housing Initiatives, 1941-1947 - Lyons, Christopher M. (Université Concordia, 2002)
Keywords: Guerre; Logement

La transmission du patrimoine au Canada (XVIIe-XVIIIe siècle): qui sont les défavorisés? - Dépatie, Sylvie (Revue d'histoire de l'Amérique française, 2001)
Keywords: Famille

La montagne, capital et intérêts - Dubé, Catherine (Continuité, 2001)
Keywords: Mont Royal; Mont-Royal (parc); Parcs

Déterminants de la valeur marchande des propriétés unifamiliales sur l'île de Montréal: évaluation de masse conjuguée aux SIG - Ozdilek, Unsal (Université du Québec à Montréal, 2001)
Keywords: Évaluation foncière

Impact des améliorations locatives sur la valeur d'un immeuble: le cas de Place Montréal Trust - Boilly, Jacques (Université du Québec à Montréal, 2000)
Keywords: Centres commerciaux

L'accès à la transaction immobilière: un des mécanismes du processus de ségrégation résidentielle ethnique - Paré, Sylvie (Recherches sociographiques, 2000)
Keywords: Logement

Housing Revitalization in Montreal: Are Condominium Conversions a Sustainable Alternative? - Swaby, Chantelle Simone (Université de Montréal, 2000)
Keywords: Logement

Les entrepreneurs en construction à Montréal au début du XXe siècle - Langlois, Jean-Yves (Université du Québec à Montréal, 1999)

Construire les infrastructures d’approvisionnement en eau en banlieue montréalaise au tournant du XXe siècle. Le cas de Saint-Louis - Poitras, Claire (Revue d'histoire de l'Amérique française, 1999)
Keywords: Aqueduc; Quartiers; Saint-Louis

Ethnicity and Home Ownership in Montreal, 1921–51 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1998)
Keywords: Locataires; Logement

"On investit et on s'investit": analyse des ressources mobilisées dans la propriété résidentielle chez un groupe de ménages de la région de Montréal - Barakatt, Guylaine (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 1998)
Keywords: Logement

Le programme de revitalisation des quartiers centraux de la ville de Montréal: analyse des impacts financiers: le cas du secteur Mile-End / Petite-Patrie - Déziel, Marie-Chantal (Université du Québec à Montréal, 1998)
Keywords: Mile End; Quartiers

Gigantism in Downtown Montreal - Gournay, Isabelle (Montreal Metropolis, 1880-1930, 1998)
Keywords: Centre-ville; Gratte-ciel; Quartiers

Manifestations du gigantisme au centre-ville - Gournay, Isabelle (Montréal métropole, 1880-1930, 1998)
Keywords: Centre-ville; Gratte-ciel; Quartiers

FORGET, sir RODOLPHE - Jedwad, Jack (Dictionnaire biographique du Canada, 1998)

Salubrious Settings and Fortunate Families: The Making of the Golden Square Mile, 1840-1895 - MacLeod, Roderick (Université McGill, 1998)
Keywords: Anglophones; Golden Square Mile; Protestants; Quartiers

PRINGLE, THOMAS - McNally, Larry S. (Dictionnaire biographique du Canada, 1998)

ROSS, JAMES - Regehr, Theodore D. (Dictionnaire biographique du Canada, 1998)

VAN HORNE, sir WILLIAM CORNELIUS - Regehr, Theodore D. (Dictionnaire biographique du Canada, 1998)

Les architectes montréalais face à la commande - Vanlaethem, France (Montréal métropole, 1880-1930, 1998)

Montreal Architects and the Challenge of Commissions - Vanlaethem, France (Montreal Metropolis, 1880-1930, 1998)

The Dominion Housing Act - Belec, John (Urban History Review / Revue d'histoire urbaine, 1997)
Keywords: Logement

The Senator, The Merchant, Two Carpenters and a Widow: A Survey of Canadian Landlords in 1871 - Burley, David G. (Urban History Review / Revue d'histoire urbaine, 1997)
Keywords: Logement

Wartime Housing as Cultural Landscape: National Creation and Personal Creativity - Evenden, Leonard J. (Urban History Review / Revue d'histoire urbaine, 1997)
Keywords: Guerre; Logement; Paysages

Industrial Efficiency, Social Order and Moral Purity: Housing Reform Thought in English Canada, 1900–1950 - Purdy, Sean (Urban History Review / Revue d'histoire urbaine, 1997)
Keywords: Logement; Réformistes

Ville St-Laurent Revisited: Wartime Housing and Architectural Change, 1942-1992 - Adams, Annmarie; Beardsley, Jennifer; Sijpkes, Pieter (School of Architecture, McGill University, 1997)
Keywords: Guerre; Logement; Saint-Laurent (ville)

Domaines « vides » et structuration morphologique de l’agglomération montréalaise - Beaudet, Gérard (Cahiers de géographie du Québec, 1997)

Les Jésuites au Sault-au-Récollet 1852-1962 - Giguère, Georges-Émile (Cahiers d'histoire du Sault-au-Récollet, 1997)
Keywords: Communautés religieuses; Jésuites; Sault-au-Récollet

Un quartier en transition - Godin, Pierre (Continuité, 1997)
Keywords: Quartiers; Vieux-Montréal

L'hôtel Bougie-Vervais - Théroux, Alain (Cahiers d'histoire du Sault-au-Récollet, 1997)
Keywords: Hôtellerie

Sûreté, salubrité et monolithisme: l'introduction du béton armé à Montréal, de 1905 à 1922 - Poitras, Claire (Urban History Review / Revue d'histoire urbaine, 1996)
Keywords: Béton

Un type de maison ouvrière: le déclin de la maison de fond de cour à Montréal, 1880-1920 - Carey, Luc (Université du Québec à Montréal, 1996)
Keywords: Logement

Les procès-verbaux de vente dans la région de Montréal au XVIIIe siècle: une étude socio-économique - Ducharme, Isabelle (Université de Montréal, 1996)

Destination, Housing and Quality of Life in the Migrant Experience from Larino (Molise, Italy) to Milano and Montreal - Fainella, John G. (Université McGill, 1996)
Keywords: Italiens; Logement

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

La dynamique de la politique du logement social à Montréal: essai d'une analyse des enjeux sociaux de l'habitat - Kuyena, Jacques-René D. (Université de Montréal, 1996)
Keywords: Logement

Montréal et son marché immobilier locatif de 1731 à 1831: stratification sociale, ségrégation spatiale et transition vers le capitalisme - Massicotte, Daniel (Université de Montréal, 1996)
Keywords: Locataires; Logement

Le peuplement de Montréal - Olson, Sherry (Atlas historique du Québec. Population et territoire, 1996)

Arsène Pigeon (1844-1908) - Prévost, Robert (Cahiers d'histoire du Sault-au-Récollet, 1996)
Keywords: Artisans; Logement; Pigeon (famille)

Land and People: Property Investment in Late Pre-Industrial - Sweeny, Robert (Urban History Review / Revue d'histoire urbaine, 1995)
Keywords: Évaluation foncière

Wartime Housing and Architectural Change, 1942-1992 - Adams, Annmarie; Sijpkes, Pieter (Canadian Folklore Canadien, 1995)
Keywords: Guerre; Logement; Saint-Laurent (ville)

Le Plateau Mont-Royal, un projet, un exploit - Knight, Alan (Continuité, 1995)
Keywords: Plateau Mont-Royal; Quartiers

Le «boom» des immeubles d’appartements à Montréal de 1921-1951 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1994)
Keywords: Logement; Outremont; Westmount

DAWES, JAMES PAWLEY - Burr, Gordon (Dictionnaire biographique du Canada, 1994)

Montréal: habitat et crise de la ville centrale - Choko, Marc H. (ARQ - Architecture Québec, 1994)

Vers un coopératisme social: la Ligue ouvrière catholique et la question du logement dans les années 1940 - Collin, Jean-Pierre (Histoire sociale / Social History, 1994)
Keywords: Ligue ouvrière catholique; Logement

JOSEPH, JACOB HENRY - Jedwab, Jack (Dictionnaire biographique du Canada, 1994)

WÜRTELE, JONATHAN SAXTON CAMPBELL - Miller, Carman (Dictionnaire biographique du Canada, 1994)

Loft Conversions in a Local Context: The Case of Inner City Montreal - Podmore, Julie (Université McGill, 1994)
Keywords: Logement

LAVIGNE, ERNEST - Poirier, Lucien (Dictionnaire biographique du Canada, 1994)

A Study of the Office Rental Buildings in Montreal: Work Paper - Bouchard, Jean (Université Concordia, 1993)
Keywords: Locataires

Entrevue avec Phyllis Lambert - Gagnon-Pratte, France (Continuité, 1993)
Keywords: Centre canadien d'architecture; Lambert, Phyllis

Community Response to Environmental Change: A Case Study of Montreal's West Island 1981-1991 - Adams, Jennifer (Université McGill, 1992)
Keywords: Quartiers; West Island

La propriété résidentielle à Montréal et à Toronto de 1921 à 1951: deux villes, deux mondes - Choko, Marc H.; Harris, Richard (Institut national de la recherche scientifique - Urbanisation, 1992)
Keywords: Logement

La Ligue ouvrière catholique et l'essor du mouvement coopératif d'habitation dans le Québec urbain, au tournant des années 1950 - Collin, Jean-Pierre (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1992)
Keywords: Ligue ouvrière catholique; Logement

Megacity Montreal - Deschamps, Yves (Continuité, 1992)
Keywords: Gratte-ciel

S'enraciner en Nouvelle-France - Dickinson, John (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

Vivre en Canada - Dickinson, John (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

La maison et son environnement - Lambert, Phyllis (Montréal, ville fortifiée au XVIIIe siècle, 1992)

The House and Its Environment - Lambert, Phyllis (Opening the Gates of Eighteenth-Century Montréal, 1992)

La conquête du ciel - Marchand, Denys (Continuité, 1992)
Keywords: Gratte-ciel

Caractéristiques spatiales des coopératives d'habitation sans but lucratif dans la ville de Montréal - Marois, Claude; Nadeau, Daniel (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Logement

Des maisons pour un autre hiver - Noppen, Luc (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

Reconstitution de la ville fortifiée du XVIIIe siècle - Stewart, Alan (Montréal, ville fortifiée au XVIIIe siècle, 1992)
Keywords: Fortifications

Reconstructing the Eighteenth-Century Town - Stewart, Alan (Opening the Gates of Eighteenth-Century Montréal, 1992)
Keywords: Fortifications

Des seigneurs missionnaires - Tremblay, Louise (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Les conditions de vie des femmes: impact du règlement de location en habitation sociale - Brais, Nicole (Université Laval, 1991)
Keywords: Femmes; Locataires; Logement

Les immeubles résidentiels à appartements multiples de type locatif à Montréal, 1889-1914 - Croteau, Danielle (Université du Québec à Montréal, 1991)
Keywords: Logement

Montréal, côté jardins - Éveillard, Catherine (Université de Montréal, 1991)
Keywords: Jardins

La métropole: à l'aube de la modernité - Germain, Annick (Cap-aux-Diamants, 1991)
Keywords: Crise; Drapeau, Jean; Houde, Camillien; Logement; Maires; Métropole

Uncompleted Condominiums: A Strategy for Cost Reduction in Montreal Housing - Kowalska, Danuta (Université McGill, 1991)
Keywords: Logement

Downtown Housing: Filling in the Gaps - MacBurnie, Ian (Grassroots, Greystones, and Glass Towers. Montreal Urban Issues and Architecture, 1991)
Keywords: Logement

Stratification sociale et différentiation spatiale en milieu urbain pré-industriel: le cas des locataires montréalais, 1731-1741 - Massicotte, Daniel (Revue d'histoire de l'Amérique française, 1991)
Keywords: Locataires

Housing That Belongs on Montreal Streets - Sheppard, Adrian (Grassroots, Greystones, and Glass Towers. Montreal Urban Issues and Architecture, 1991)
Keywords: Logement

Mutual Aid Networks in Two Feminist Housing Co-Operatives in Montreal - Yasmeen, Gisèle (Université McGill, 1991)
Keywords: Féminisme; Logement

La transmission du patrimoine dans les terroirs en expansion: un exemple canadien au XVIII siècle - Dépatie, Sylvie (Revue d'histoire de l'Amérique française, 1990)
Keywords: Famille

Les gratte-ciel de Montréal - Forget, Madeleine (Éditions du Méridien, 1990)
Keywords: Gratte-ciel

BROWNE, JOHN JAMES - Gersovitz, Julia (Dictionnaire biographique du Canada, 1990)

L'évolution de l'habitat montréalais - Hanna, David B. (Montréal au XIXe siècle. Des gens, des idées, des arts, une ville, 1990)
Keywords: Logement

VIAU, CHARLES-THÉODORE - Linteau, Paul-André (Dictionnaire biographique du Canada, 1990)

Les architectes et l'introduction du béton armé à Montréal de 1900 à 1930 - Poitras, Claire (Université de Montréal, 1990)
Keywords: Béton

SHANLY, WALTER - Stanley, Laurie C.C.; Blackwell, John D. (Dictionnaire biographique du Canada, 1990)

NOTMAN, WILLIAM - Triggs, Stanley G. (Dictionnaire biographique du Canada, 1990)

Modular Prefabrication versus Conventional Construction as a Cost Effective Alternative for the Construction of Single Family Detached Housing in the Montreal Area - Wiedemann, Stefan J. (Université McGill, 1990)
Keywords: Logement

Housing That Belongs on Montreal Streets - Sheppard, Adrian (Grassroots, Greystones, and Glass Towers. Montreal Urban Issues and Architecture, 1989)
Keywords: Logement

La mobilité résidentielle au centre de l'île de Montréal: essai de géographie sociale - Awada, Atef (Université de Montréal, 1988)
Keywords: Mobilité résidentielle

PAPINEAU, JOSEPH - Chabot, Richard (Dictionnaire biographique du Canada, 1988)

La modernisation de la société québécoise dans les années cinquante: le cas des coopératives d'habitation - Collin, Jean-Pierre (Georges-Émile Lapalme, 1988)
Keywords: Logement

Housing without Families: The Housing Situation of Non-Family Households in Montreal - Lavigne, Jean-François (Université McGill, 1988)
Keywords: Logement

CHRISTIE, WILLIAM PLENDERLEATH - Noël, Françoise (Dictionnaire biographique du Canada, 1988)

MASSON, JOSEPH - Ouellet, Fernand (Dictionnaire biographique du Canada, 1988)

Les activités de bureau à Montréal: structure, évolution et perspectives d'avenir - Polese, Mario (Ville de Montréal, Service de la planification et de la concertation, 1988)
Keywords: Centre-ville; Quartiers

POTHIER, TOUSSAINT - Pothier, Philippe (Dictionnaire biographique du Canada, 1988)

Settling an 18th Century Faubourg: Property and Family in the Saint-Laurent Suburb, 1735-1810 - Stewart, Alan M. (Université McGill, 1988)
Keywords: Famille; Faubourgs; Quartiers; Saint-Laurent (quartier)

DELORME, CHARLES-SIMON - Tremblay, Robert (Dictionnaire biographique du Canada, 1988)

L'abitazione e la rivoluzione industriale: Montréal nella seconda metà dell' 800 - Hanna, David B. (Storia urbana, 1987)
Keywords: Logement

GIBB, BENAIAH - Burgess, Joanne (Dictionnaire biographique du Canada, 1987)

Crise du logement et action catholique à Montréal, 1940-1960 - Collin, Jean-Pierre (Revue d'histoire de l'Amérique française, 1987)
Keywords: Coopérative d'habitation de Montréal; Ligue ouvrière catholique; Logement

Histoire et analyse des premières générations de gratte-ciel à Montréal, 1888-1930 - Forget, Madeleine (Université du Québec à Montréal, 1987)
Keywords: Gratte-ciel

SEWELL, STEPHEN - Greenwood, F. Murray (Dictionnaire biographique du Canada, 1987)

CHARTIER DE LOTBINIÈRE, MICHEL-EUSTACHE-GASPARD-ALAIN - Hamelin, Marcel (Dictionnaire biographique du Canada, 1987)

Montreal, a City Built by Small Builders, 1867-1880 - Hanna, David B. (Université McGill, 1987)
Keywords: Logement

LOEDEL, HENRY NICHOLAS CHRISTOPHER - Janson, Gilles (Dictionnaire biographique du Canada, 1987)

McCORD, THOMAS - Kyte Senior, Elionor (Dictionnaire biographique du Canada, 1987)

Essai d'une méthode d'analyse typo-morphogénétique de l'information du bâti par le loti: les îlots et les sections de rue du quartier Saint-Jean-Baptiste à Montréal - La Rue, Pierre (Université de Montréal, 1987)
Keywords: Quartiers; Saint-Jean-Baptiste (village)

CHAUSSEGROS DE LÉRY, LOUIS-RENÉ - Legault, Roch (Dictionnaire biographique du Canada, 1987)

La maison de bois - Léonidoff, Georges-Pierre (Atlas historique du Canada. Volume I. Des origines à 1800, 1987)

Les maisons, 1660-1800 - Léonidoff, Georges-Pierre (Atlas historique du Canada. Volume I. Des origines à 1800, 1987)

McKINDLAY, JOHN - Macmillan, David D. (Dictionnaire biographique du Canada, 1987)

Le marché du logement locatif à Montréal de 1731 à 1741 - Massicotte, Daniel (Université de Montréal, 1987)
Keywords: Locataires; Logement

GRAY, JOHN - Miller, Carman (Dictionnaire biographique du Canada, 1987)

ERMATINGER, FREDERICK WILLIAM - Momryk, Myron (Dictionnaire biographique du Canada, 1987)

SUTHERLAND, DANIEL - Momryk, Myron (Dictionnaire biographique du Canada, 1987)

McGILLIVRAY, WILLIAM - Ouellet, Fernand (Dictionnaire biographique du Canada, 1987)

Les habitants de Montréal et de Québec (1790-1835): contextes géo-économiques différents, même stratégie foncière - Paquet, Gilles; Wallot, Jean-Pierre (Sociétés villageoises et rapports villes-campagnes au Québec et dans la France de l'ouest XVIIe-XXe siècles, 1987)

BERTHELET, PIERRE - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1987)

GATES, HORATIO - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1987)

DAVID, DAVID - Senior, Elinor Kyte (Dictionnaire biographique du Canada, 1987)

JOHNSON, sir JOHN - Thomas, Earle (Dictionnaire biographique du Canada, 1987)

Le logement et les enjeux de la transformation de l'espace urbain: Montréal, 1940-1960 - Choko, Marc H.; Collin, Jean-Pierre; Germain, Annick (Urban History Review / Revue d'histoire urbaine, 1986)
Keywords: Logement

La Cité coopérative canadienne-française: Saint-Léonard-de-Port-Maurice, 1955-1963 - Collin, Jean-Pierre (Presses de l'Université du Québec/INRS-Urbanisations, 1986)
Keywords: Coopérative d'habitation de Montréal; Logement; Quartiers; Saint-Léonard

Ethnicity and Housing Adaptation: the Italians in Montreal - Fainella, John G. (Université McGill, 1986)
Keywords: Italiens; Logement

The Layered City: A Revolution in Housing in Mid-Nineteenth-Century Montreal - Hanna, David B. (Université McGill, Département de géographie, 1986)
Keywords: Logement

A City of Tenants: Home-ownership and Social Class in Montreal, 1847-1881 - Hertzog, Stephen; Lewis, Robert D. (The Canadian Geographer / Le Géographe canadien, 1986)
Keywords: Locataires; Logement

Bâtir ensemble: historique du mouvement coopératif en habitation dans Hochelaga-Maisonneuve - Labrecque, Francine (Atelier d'histoire Hochelaga-Maisonneuve, 1986)
Keywords: Hochelaga (quartier); Logement; Maisonneuve; Quartiers

L'évolution de l'occupation du parc résidentiel plus ancien de Montréal de 1951 à 1979 - Mathews, Georges (INRS-Urbanisation, 1986)
Keywords: Logement

Les familles à faible revenu et le problème du logement: développement potentiel des coopératives d'habitation à Montréal - Nadeau, Daniel (Université de Montréal, 1986)
Keywords: Logement

Les coûts d'habitat: un critère d'urbanisme? - Achour, Dominique; Divay, Gérard (INRS-Urbanisation, Presses de l'Université du Québec, 1985)
Keywords: Logement

Montreal Chinese Property Ownership and Occupational Change, 1881-1981 - Aiken, Rebecca Bruff (Université McGill, 1985)
Keywords: Chinois; Travail

PAPINEAU, DENIS-BENJAMIN - Baribeau, Claude (Dictionnaire biographique du Canada, 1985)

VOYER, ANTOINE - Bernier, Paul (Dictionnaire biographique du Canada, 1985)

MORRIS, WILLIAM - Bridgman, Harry (Dictionnaire biographique du Canada, 1985)

McKAY, THOMAS - Bush, E.F. (Dictionnaire biographique du Canada, 1985)

McDONALD, ARCHIBALD - Cole, Jean Murray (Dictionnaire biographique du Canada, 1985)

VIGER, LOUIS-MICHEL - De Lorimier, Michel (Dictionnaire biographique du Canada, 1985)

GERRARD, SAMUEL - Deslauriers, Peter (Dictionnaire biographique du Canada, 1985)

A City of Tenants: Home-Ownership and Social Class in Montreal, 1847-1881/Une ville de locataires : propriété résidentielle et classes sociales à Montréal de 1847 à 1881 - Hertzog, Stephen (Université McGill, Departement de géographie, 1985)
Keywords: Locataires; Logement

HART, BENJAMIN - Miller, Carman (Dictionnaire biographique du Canada, 1985)

THOMPSON, DAVID - Nicks, John (Dictionnaire biographique du Canada, 1985)

BARBIER, LOUIS-MARIE-RAPHAËL - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1985)

McCORD, WILLIAM KING - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1985)

VIGER, JACQUES - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1985)

An Empirical Investigation of Condominium Buying in the Montréal Area - Constantineau, Pierre (Université Concordia, 1984)

State Intervention and Alternative Tenure Patterns in Montreal - Dansereau, Francine; Godbout, Jacques; Divay, Gérard (INRS-Urbanisation, 1984)
Keywords: Logement

La formation des espaces résidentiels. Le système de production de l'habitat urbain dans les années soixante-dix au Québec - Divay, Gérard; Gaudreau, Marcel (INRS-Urbanisation, Presses de l'Université du Québec, 1984)
Keywords: Logement

A Stake in the System: Domestic Property Ownership and Social Class in Montreal, 1847-1881 - Hertzog, Stephen (Université McGill, 1984)
Keywords: Logement

Quartier ethnique et propriété foncière: le cas de la communauté italienne de Montréal - Laplace, Gérard (Université de Montréal, 1984)
Keywords: Italiens; Logement; Quartiers

Le contrôle de l'espace et du bâti dans la banlieue montréalaise (1840-1914) - Linteau, Paul-André (Habiter la ville, XVe-XXe siècles, 1984)
Keywords: Banlieue

Land Ownership and Society in Montreal: An Hypothesis - Linteau, Paul-André; Robert, Jean-Claude (The Canadian City: Essays in Urban and Social History, 1984)

Métiers, loyers et bouts de rue: l'armature de la société montréalaise, 1881 à 1901 - Hanna, David B.; Olson, Sherry (Cahiers de géographie du Québec, 1983)
Keywords: Logement

ROBERTSON, DANIEL - Armour, David Arthur (Dictionnaire biographique du Canada, 1983)

FORETIER, PIERRE - Burgess, Joanne (Dictionnaire biographique du Canada, 1983)

ELLICE, ALEXANDER - Colthart, James M. (Dictionnaire biographique du Canada, 1983)

McGILL, JAMES - Cooper, John Irwin (Dictionnaire biographique du Canada, 1983)

HAZEN, MOSES - Everest, Allan S. (Dictionnaire biographique du Canada, 1983)

Logement et luttes urbaines à Montréal (1963-1976) - Hamel, Pierre (Université de Montréal, Faculté de l'aménagement, 1983)
Keywords: Groupes populaires; Logement

BLAKE, CHARLES - Janson, Gilles (Dictionnaire biographique du Canada, 1983)

GUY, PIERRE - Joanette, Ginette; John, Claire (Dictionnaire biographique du Canada, 1983)

CHARLAND, LOUIS - Langelier, Gilles (Dictionnaire biographique du Canada, 1983)

TODD, ISAAC - Momryk, Myron (Dictionnaire biographique du Canada, 1983)

FROBISHER, JOSEPH - Ouellet, Fernand (Dictionnaire biographique du Canada, 1983)

McTAVISH, SIMON - Ouellet, Fernand (Dictionnaire biographique du Canada, 1983)

25 ans de logement social à Montréal - Beaupré, Pierre (ARQ - Architecture Québec, 1982)
Keywords: Logement

BEAUBIEN, PIERRE - Bernier, Jacques (Dictionnaire biographique du Canada, 1982)

MacDOUGALL, DUGALD LORN - Doyon, Charles (Dictionnaire biographique du Canada, 1982)

Comportement économique des "propriétaires" et "locataires" d'origine canadienne et étrangère dans un secteur résidentiel éloigné du centre-ville de Montréal - Dugas, Gilles (Université de Montréal, 1982)
Keywords: Locataires

BARLOW, ROBERT - Eagan, William E. (Dictionnaire biographique du Canada, 1982)

RODIER, CHARLES-SÉRAPHIN - Linteau, Paul-André (Dictionnaire biographique du Canada, 1982)

DAVID, FERDINAND - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1982)

MUNRO, HECTOR - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1982)

Crise du logement et capital immobilier: Montréal. Le redéveloppement du centre-ville de 1957 à nos jours et ses conséquences - Choko, Marc H. (Université de Paris VIII, 1981)
Keywords: Centre-ville; Logement; Quartiers

Working Class Housing in Montreal, 1940-1980 - Melamed, Andy (Montreal Geographical Essays, 1981)
Keywords: Logement

Creation of an Early Victorian Suburb in Montreal - Hanna, David B. (Urban History Review / Revue d'histoire urbaine, 1980)
Keywords: Banlieue; Golden Square Mile; Logement; Quartiers

L'histoire du logement ouvrier à Hochelaga-Maisonneuve - Atelier d'histoire Hochelaga-Maisonneuve (L'Atelier, 1980)
Keywords: Hochelaga (quartier); Logement; Maisonneuve

L'habitation collective et la copropriété indivise - Brahimi, Sylvia (Université de Montréal, 1980)
Keywords: Logement

Crises du logement à Montréal, 1860-1939 - Choko, Marc H. (Éditions coopératives Albert Saint-Martin, 1980)
Keywords: Logement

Développement économique urbain: propriété foncière et le centre-ville de Montréal de 1890 à 1908 - Drouin, Jacques (Université de Montréal, 1980)
Keywords: Centre-ville; Quartiers

COURREAUD (Courraud) DE LA COSTE (La Côte), PIERRE - Igartua, José (Dictionnaire biographique du Canada, 1980)

Évolution générale du marché du logement de la région de Montréal de 1951 à 1976: données synthétiques sur une réussite méconnue - Mathews, Georges (INRS-Urbanisation, 1980)
Keywords: Logement

SANGUINET, SIMON - Tremblay, Yves-Jean (Dictionnaire biographique du Canada, 1980)

L'habitation et l'évolution de l'urbanisme à Montréal: de la grande dépression à la création de la Société d'habitation du Québec, 1935-1968 - Perreault, Louis (Université Laval, 1979)
Keywords: Logement

The Movement for Public Housing in Montreal, 1930-1958 - Ruddick, Susan M. (Université McGill, 1979)
Keywords: Logement

La ségrégation résidentielle ethnique à Montréal - Lapointe, Alain (Université des sciences sociales de Toulouse, 1978)

L'impact de l'immigration sur le marché du logement dans la région métropolitaine de Montréal de 1961 à 1981 - Mathews, Georges (Gouvernement du Québec, ministère de l'Immigration, 1978)
Keywords: Logement

Analyse du développement résidentiel en hauteur à Montréal 1961-1975: schéma d'organisation et étude des agents de production - Moulin, Charles (Université de Montréal, 1978)
Keywords: Logement

Les vrais propriétaires de Montréal - Aubin, Henry (L'Étincelle, 1977)

L'évolution du marché foncier en périphérie du centre-ville de Montréal au cours des années soixante - Collin, Jean-Pierre; Dansereau, Francine (INRS-Urbanisation, 1977)

ELLICE, EDWARD - Colthart, James M. (Dictionnaire biographique du Canada, 1977)

MOLSON, THOMAS - Dubuc, Alfred (Dictionnaire biographique du Canada, 1977)

"The New Town of Montreal". Creation of an Upper Middle Class Suburb on the Slope of Mount Royal in the Mid-Nineteenth Century - Hanna, David B. (Université de Toronto, 1977)
Keywords: Golden Square Mile; Logement; Quartiers

Land Ownership and Society in Montreal: An Hypothesis - Linteau, Paul-André; Robert, Jean-Claude (The Canadian City : Essays in Urban History, 1977)

LA FONTAINE (Ménard, dit La Fontaine), sir LOUIS-HIPPOLYTE - Monet, Jacques (Dictionnaire biographique du Canada, 1977)

VIGER, DENIS-BENJAMIN - Ouellet, Fernand; Lefort, André (Dictionnaire biographique du Canada, 1977)

BOYER, LOUIS - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1977)

REDPATH, JOHN - Tulchinsky, Gérald Jacob Joseph (Dictionnaire biographique du Canada, 1977)

DONEGANI, JOHN ANTHONY - Young, Brian J. (Dictionnaire biographique du Canada, 1977)

La détérioration résidentielle à Montréal - Deschambault, Gabriel (Université de Montréal, 1976)
Keywords: Logement

L'évolution des valeurs foncières à Montréal, (1964-1969) - Foggin, Peter M. (Cahiers de géographie du Québec, 1975)
Keywords: Évaluation foncière

Landlord Subsidization by Tenants in East End Montreal - Kovitz, Marcia Mitzi Ruth (Université McGill, 1975)
Keywords: Locataires; Logement

Residential Rehabilitation - with Special Reference to Montreal - Santiago, Arturo M. (Université McGill, 1975)
Keywords: Logement

Le marché du logement à Montréal - Bouchard, Pierre (Université de Montréal, 1974)
Keywords: Logement

Propriété foncière et société à Montréal: une hypothèse - Linteau, Paul-André; Robert, Jean-Claude (Revue d'histoire de l'Amérique française, 1974)

JANSON, Lapalme, DOMINIQUE - Moogk, Peter N. (Dictionnaire biographique du Canada, 1974)

Development of High-Rise Habitation in Central Urban Areas with Special Reference to Montreal - Raina, S. K. (Université McGill, 1974)
Keywords: Logement

CHARLY SAINT-ANGE, LOUIS - Standen, S. Dale (Dictionnaire biographique du Canada, 1974)

Logement et rénovation urbaine à Montréal - Ziolko, Caroline (Université de Montréal, 1974)
Keywords: Logement

Private Rehabilitation in a Low Rent Area: Landlord-Tenant Relations and other Non-Market Factors - Duff, Huntly Douglas (Université McGill, 1973)
Keywords: Locataires; Logement; Portugais

REGNAUD, FRANÇOIS-JOSEPH-VICTOR - Audet, Louis-Philippe (Dictionnaire biographique du Canada, 1972)

Neighbourhood Economy and the Urban Housing Problem: Landlords and Tenants in a Working Class Montreal Locality - Fleming, C. E. B.; Krohn, R. G. (The Western Canadian Journal of Anthropology, 1972)
Keywords: Locataires; Logement

The Social Organization of Residential Real Estate - House, John Douglas (Université McGill, 1972)

BAGG, STANLEY CLARK - Landry, Pierre B. (Dictionnaire biographique du Canada, 1972)
Keywords: Archéologie; Juges; Notaires; Numismatie

BERTHELET, OLIVIER - Pouliot, Léon (Dictionnaire biographique du Canada, 1972)

The Ownership of Old Rental Housing in an Appreciating Central Montreal Neighborhood - Roberts, Marilyn Manzer (Université McGill, 1972)
Keywords: Logement

Spatial Aspects of Real Estate Transactions an Exploratory Study of the Island of Montreal: 1947-1967 - De Jong, Nicolas J. (Université McGill, 1971)

Spatial Aspects of Real Estate Transactions: An Exploratory Study of the Island of Montreal, 1947-1967 - Dejong, Nicolas J. (Université McGill, 1971)

Montréal: bilan décennal d'une morphologie en transition - Denis, Paul-Yves (Revue de Géographie de Montréal, 1971)

Ville de Montréal: édifices à bureau 1949-1969 (Hôtel de ville, Bureau des recherches économiques, 1970)

Design Considerations in Urban Low-Income Housing Redevelopment with Special Reference to Montreal - Chan, David Wai (Université McGill, 1970)
Keywords: Logement

Changes in the Intra-Urban Land-Value Surface: The Impact of Transportation, Land-Use and Socio-Economic Factors in Central Montreal - Foggin, Peter M. (Université McGill, 1970)

VOLANT DE RADISSON, ÉTIENNE - Bond, Courtney C. J. (Dictionnaire biographique du Canada, 1969)

VACHON DE BELMONT, FRANÇOIS - Mathieu, Jacques (Dictionnaire biographique du Canada, 1969)

COUAGNE, CHARLES DE - Nish, Cameron (Dictionnaire biographique du Canada, 1969)

LE CONTE DUPRÉ, LOUIS - Nish, Cameron (Dictionnaire biographique du Canada, 1969)

La cohabitation à Montréal: une étude sur les attitudes vis-à-vis la cohabitation de 92 typographes canadien-français et propriétaires de leur maison - Bélair, Claudette (Université de Montréal, 1966)
Keywords: Locataires; Logement

De la maison unifamiliale en rangée dans la banlieue de Montréal - Bourque, Maurice R. (Université de Montréal, 1966)
Keywords: Banlieue; Logement

CAVELIER DE LA SALLE, RENÉ-ROBERT - Dupré, Céline (Dictionnaire biographique du Canada, 1966)

BAILLY, Lafleur, FRANÇOIS - Gowans, Alan (Dictionnaire biographique du Canada, 1966)

BASSET DES LAURIERS, BÉNIGNE - Lefebvre, Jean-Jacques (Dictionnaire biographique du Canada, 1966)

The Development of Complex Commercial Projects in Central Areas with Special Reference to Montreal - Ng, Spencer Che Lou (Université McGill, 1965)
Keywords: Gratte-ciel

Housing in the Suburban Region of Montreal, 1951-1961 - Dernoi, Louis Anthony (Université McGill, 1964)
Keywords: Banlieue; Logement

Space about Multiple Dwellings with Special Reference to Montreal - Steber, George Jr. (Université McGill, 1963)
Keywords: Logement

Social Mobility in the Home-Building Industry in Montreal, 1951-1961 - Rawin, Solomon John (Université McGill, 1962)
Keywords: Logement

Le besoin de logement à Montréal - Germain, Denis (L'Actualité économique, 1961)
Keywords: Logement

Les baux à ferme à Montréal au XVIIe siècle - Leroux, Gilbert (Themis, 1959)
Keywords: Baux à ferme

Messieurs de Saint-Sulpice devant le Conseil Souverain en 1667 (leurs titres de propriété) - Langlais, Antonio (Revue d'histoire de l'Amérique française, 1957)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Le logement familial à prix modique à Montréal - Gauthier, Paul (Université de Montréal, 1949)
Keywords: Logement

Le logement à Montréal des étudiants forains à l'Université de Montréal et son incidence au point de vue social sur la vie étudiante - Beaugrand-Champagne, Guy (Université de Montréal, 1948)
Keywords: Logement; Université de Montréal; Étudiants

L'habitation à Montréal - Deschamps, Jean (L'Actualité économique, 1947)
Keywords: Logement

Valeur de la propriété immobilière détenue par les Canadiens français dans la région métropolitaine de Montréal - Saint-Pierre, Arthur (Mémoires et comptes rendus de la Société royale du Canada, 1947)
Keywords: Francophones; Logement

Le problème du logement à Montréal: le taudis, facteur de délinquence et de tuberculose - Fortin, Berthe (Université de Montréal, 1946)
Keywords: Délinquance; Logement; Tuberculose

Pierre Berthelet and his Family (in Canada and in the United States) - Fabre-Surveyer, Edouard (Mémoires et comptes rendus de la Société royale du Canada, 1943)
Keywords: Berthelet (famille); Berthelet, Pierre

L'impôt foncier à Montréal - Charbonneau, Roger (L'Actualité économique, 1940)
Keywords: Fiscalité; Impôt foncier

Le problème de la petite propriété à Montréal - Martin, René (L'Actualité économique, 1939)
Keywords: Logement

The Construction Industry in Montreal with Special Reference to Seasonal Unemployment - Berman, Alfred (Université McGill, 1931)
Keywords: Chômage

Maçons, entrepreneurs, architectes - Massicotte, E.-Z. (Bulletin des recherches historiques, 1929)
Keywords: Maçons

L'habitation à Montréal - Cousineau, A. (Revue trimestrielle canadienne, 1920)
Keywords: Logement

Les arpenteurs de Montréal. Addenda - Massicotte, E.-Z. (Bulletin des recherches historiques, 1919)
Keywords: Arpenteurs

Les arpenteurs de Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1918)
Keywords: Arpenteurs